Uso de aplicativos para o ensino de Matemática na EJA: possibilidades e desafios - Rossi, Nara Venâncio (Universidade Federal de São Carlos, 2021)
This final course paper aims to investigate the possibilities of using applications for the development of digital skills, mathematical literacy skills and learning satisfaction in EJA classes described in articles, dissertations and monographs. A qualitative, bibliographical research of exploratory nature was carried out, for data analysis the steps of reading by Gil (2017) were followed. As a result, we have that the use of applications contributed to the development of skills by providing means of accessing the internet and the use of computers and cell phones, by promoting reflection on how technology contributes to solving problems; to provide reflection on the different ways that Mathematics is inserted in people's lives, its usefulness and contributions; understand concepts and master procedures necessary to know how to do mathematics; by arousing students' interest and curiosity, combined with useful and meaningful knowledge. It is concluded that the use of applications for teaching mathematics in EJA brings more possibilities than challenges.
Use of apps for teaching Mathematics at EJA: possibilities and challenges
Keywords: Pesquisa bibliográfica; Educação de jovens e adultos; Letramento matemático; Tecnologias; Bibliographical research; Adult education; Mathematical literacy; Tecnologies; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM